Taá¹hwÄ«r MawÄd MahÄrah al-KitÄbah bi á¹¬harÄ«qah Luâ€™bah Khimna al-Kalimah fÄ« Shuâ€™bah al-DÄ«niyah Min Madrasah al-â€˜Ä€Liyah al-HukÅ«miyah 1 Probolinggo - Firdaus, Sulton; Isnol Khotimah; Aviah Asmaâ€™ul Hosna (Universitas Yudharta Pasuruan, 2022)
Arabic learning as a source of Islamic development needs publication with written works. However, there are obstacles in writing skills such as the use of words that are not in accordance with the rules, and most students memorize vocabulary without knowing how to write them. So the objectives of this research are: 1. To provide material for creative writing skills using the game method. 2. Knowing the effectiveness of using the designed method. The researcher uses the Dick and Carey model of research and development approach with stages: defining goals, conducting learning analysis, students, formulating specific goals, developing assessment tools, educational strategies, selecting teaching materials, carrying out formative evaluations, and reviewing instructions. The results of the study: 1. learning writing skills in the religious program of MAN 1 Probolinggo in schools and dormitories. 2. Material development using a guessing game model with Arabic script with rules. Consists of: (a) guides and accompanying books used. (b) Lesson plan. 3. The designed model is effective to use. based on statistical analysis of students' responses and understanding before using the designed method with an average test result of 81.5 pre-test and after using the method with a post-test average of 86.16.